Exponential Clonal Expansion of 5-Fluorocytosine–Resistant Candida tropicalis and New Insights into Underlying Molecular Mechanisms - Nissrine Abou-Chakra; Karen Marie Thyssen Astvad; Jan Martinussen; Amalie Sofie Eilsø Munksgaard; Maiken Cavling Arendrup (Emerging Infectious Diseases)
In 2022, we initiated systematic 5-fluorocytosine susceptibility testing of Candida spp. isolates in Denmark; we observed a bimodal MIC distribution in C. tropicalis, with MICs >16 mg/L in half the isolates. This study investigates the epidemiology and molecular mechanisms of 5-fluorocytosine resistance in C. tropicalis. We analyzed 104 C. tropicalis isolates from 3 time periods, alongside 353 C. albicans and 227 C. glabrata isolates from 2022. We determined MICs using EUCAST E.Def 7.3. Sequencing of FCY2 (purine-cytosine permease), FCY1 (cytosine deaminase), FUR1 (uracil phosphoribosyl transferase), and URA3 (orotidine-5′-phosphate decarboxylase) genes revealed FCY2 alterations—E49X (30/32), Q7X (1/32), and K6NfsX10 (1/32)—in resistant C. tropicalis strains. We found a URA3 alteration, K177E, in both susceptible and resistant strains. Microsatellite genotyping showed that all C. tropicalis isolates with E49X were clonally related. The marked increase in resistance, driven by the clonal spread of E49X, necessitates further research into virulence and environmental factors.